The Influence of the Work Environment on Employee Performance Through Organizational Citizenship Behavior (OCB) in Surabaya Region III Airport Authority Employees - Fadhilah Eviana Putri; Ika Fathin Resti Martanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
All organizations will definitely require all employees to always develop and optimize every effort so that the performance results achieved can be maximized. To maximize performance, it needs to be supported by a good work environment. The better the work environment in the company results in the better the Organizational Citizenship Behavior (OCB) of employees which will improve performance. This study aims to determine the effect of the work environment on employee performance through Organizational Citizenship Behavior (OCB) in Region III Airport Authority employees. This study used a quantitative method with data collection techniques using a questionnaire. The population in this study is 150 Civil Servants of the Airport Authority Office Region III with a sample of 109 obtained using the slovin formula calculation. Data analysis techniques were performed using SPSS software version 15.0. The results of this study indicate that: (1) there is a significant influence between the work environment on OCB; (2) there is a significant influence between OCB on performance; (3) there is a significant effect of work environment on performance; and (4) there is no indirect effect of work environment on performance through OCB as an intervening variable.